Cassava Starch-Onion Peel Powder Biocomposite Films: Functional, Mechanical, and Barrier Properties for Biodegradable Packaging - Torche, Assala; Chouana, Toufik; Bensalem, Soufiane; Khaled, Meyada; Laid Rekbi, Fares Mohammed; Kelai, Elyes; Rastrelli, Luca (Mdpi, 2025)
This study valorizes onion peel, an agro-industrial by-product rich in phenolic compounds and structural carbohydrates, for the development of cassava starch-based biodegradable films. The films were prepared using the solution casting method; a cassava starch matrix was mixed with a 2.5% glycerol solution and heated to 85 degrees C for 30 min. A separate solution of onion peel powder (OPP) in distilled water was prepared at 25 degrees C. The two solutions were then combined and stirred for an additional 2 min before 25 mL of the final mixture was cast to form the films. Onion peel powder (OPP) incorporation produced darker and more opaque films, suitable for packaging light-sensitive foods. Film thickness increased with OPP content (0.138-0.218 mm), while moisture content (19.2-32.6%) and solubility (24.0-25.2%) decreased. Conversely, water vapor permeability (WVP) significantly increased (1.69 x 10(-9)-2.77 x 10(-9) gm(-1)s(-1)Pa-1; p < 0.0001), reflecting the hydrophilic nature of OPP. Thermal analysis (TGA/DSC) indicated stability up to 245 degrees C, supporting applications as food coatings. Morphological analysis (SEM) revealed OPP microparticles embedded in the starch matrix, with FTIR and XRD suggesting electrostatic and hydrogen-bond interactions. Mechanically, tensile strength improved (up to 2.71 MPa) while elongation decreased (14.1%), indicating stronger but less flexible films. Biodegradability assays showed slightly reduced degradation (29.0-31.8%) compared with the control (38.4%), likely due to antimicrobial phenolics inhibiting soil microbiota. Overall, OPP and cassava starch represent low-cost, abundant raw materials for the formulation of functional biopolymer films with potential in sustainable food packaging.
Keywords: onion peel; starch; waste; biodegradable packaging; biodegradability